(Literary) Capital of the Russian Arctic: Murmansk in Russian Literature - Lappela, Anni Irmeli (Poljarnyj vestnik, 2018)
In this article, I examine depictions of the city of Murmansk in Soviet and contemporary Russian literature: how different works describe Murmansk’s liminal location and role as a frontier city in the Russian Arctic. I approach this question by analyzing three themes central in the texts about Murmansk: 1) future visions of the city, 2) the role of the sea/ocean and the port in the city life, and 3) depictions of the geographical location and natural surroundings of the city. I ask how the image of the city may have changed during the last century and how different actors and places in the city space influence the urban experiences of the protagonists. The Arctic became “a key component of the modern mythology” in the Soviet Union in the 1930s (McCannon 1998: 81). This “Arctic myth”, examined extensively by John McCannon (1998, 2003), is an important context for my study. I am interested in the role of urbanization, focusing on the city of Murmansk, in the Arctic myth and in conquering the North in the 1930s. I also cover questions about the relationship between gender and urban space in this Arctic city text. My theoretical frameworks come from literary urban studies, geocriticism, ecocriticism and semiotics. I analyze Soviet texts in parallel with the contemporary material. The geocritic Bertrand Westphal proposes the geocentered approach to texts: “the geocritical study of literature is not organized around texts or authors but around geographic sites” (Prieto 2011: 20, italics mine). According to Westphal, analyzing a single text or a single author makes the study of a place lopsided, and geocritical study should emphasize the space more than an observer (Westphal 2011: 126, 131, italics mine). Applying Westphal’s geocentered approach to texts, I analyze depictions of Murmansk in multiple texts from different authors and decades. I prefer this kind of approach because exploring different eras’ texts about Murmansk, I want to give a comparative perspective to the history of Murmansk as a literary city.